TRENDS OF BLUE ECONOMIC STUDY RESEARCH: ONE-DECADE SYSTEMATIC REVIEW - Syifa Fajar Maulani; Rubby Rahman Tsani; Ricko Christian Hotlan Tinambunan; Fikri Muhammad Mauluddin (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
A sustainable economic concept is needed in order to save Indonesia's marine ecosystem, but still, be able to prosper its people. The economic concept is summarized in the term Blue Economy. This type of research uses descriptive qualitative. The research method is a literature study with a bibliometric analysis approach. This research was conducted to find out the number of blue economy publications, to understand the terms that often appear in research related to the blue economy. The object of the research is the bibliographical manuscript data obtained from Google Scholar which has been systematically researched in a decade using the Publish or Perish application, then mapped and analyzed using Vos Viewer software. The search results for the journal number of publications with the keyword "Blue Economy" for 10 years, amounted to 75 journals and 2019 was the peak of publication. The results of the bibliometric analysis show that there are 165 terms related to the blue economy and are divided into 8 clusters. The keyword blue economy is closely related to marine, ocean, inclusion, coastal economics, ocean economy, and sustainability. This is in accordance with the understanding conveyed by the initiators of the Blue Economy, namely Gunter Pauli and Everest Philip